(3QLGd GdHQbjs - (3GdHQbj, CoHh LYaQ GHf CHj YHO Gddg, CMeO Hf eMeO Hf NGdO, J (B274 (3g`s ((3MSf Hf YHO GdgGOj Hf ehSi GdehShj GdNQSGfjs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3CUMGH QShd Gddg Udi Gddg Ydjg hSde ; SdeGf Hf GdESdGe ehdi QShd Gddg hGdebOGO Hf YeQh hcGf GdCShO Hf YHO jZhK JHfGg jfSH Edjg hCHh PQ GdZaGQj (B...s
(3BNQgG (B:s
... (3Ue bGd dG CSeY QLdG jbhd eKd ebGdJg Jdc EdG VQHJ Yfbg Ke eVi gh hSGde heYGP Hf LHd hCHh YHjOI TGgQjf Sjhajge MJi GNQLhG CHhHcQ hCUYOhg GdefHQ (B.s
(3efbhdI Yf fSNI (B: (3GdTjN TjQ eMeO Hf UaQ Ydj GdgePGfj GdLhQbGfj Yf fSNI Yf fSNI Yf fSNI HNW GdeUfas
(3JHUQI GdeDda (B:s
(3KeI NdGa cHjQ Mhd eDda GdcJGH Hjf GdGHf CMeO hGdCH eMeO Hd hSY HYVge GdZdGb CcKQ ef Pdcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\205s
(3gOjI GdYGQajf (B1 \67s
Keywords: (3GdMOjK hGdeUWdMs